A 70% Ethanol Extract of Mistletoe Rich in Betulin, Betulinic Acid, and Oleanolic Acid Potentiated β-Cell Function and Mass and Enhanced Hepatic Insulin Sensitivity - Ko, Byoung-Seob (Evid Based Complement Alternat Med, 2016)
We investigated that the long-term consumption of the water (KME-W) and 70% ethanol (KME-E) mistletoe extracts had antidiabetic activities in partial pancreatectomized (Px) rats. Px rats were provided with a high-fat diet containing 0.6% KME-E, 0.6% KME-W, and 0.6% dextrin (control) for 8 weeks. As normal-control, Sham-operated rats were provided with 0.6% dextrin. In cell-based studies, the effects of its main terpenoids (betulin, betulinic acid, and oleanolic acid) on glucose metabolism were measured. Both KME-W and KME-E decreased epididymal fat mass by increasing fat oxidation in diabetic rats. KME-E but not KME-W exhibited greater potentiation of first-phase insulin secretion than the Px-control in a hyperglycemic clamp. KME-E also made β-cell mass greater than the control by increasing β-cell proliferation and decreasing its apoptosis. In a euglycemic-hyperinsulinemic clamp, whole-body glucose infusion rate and hepatic glucose output increased with potentiating hepatic insulin signaling in the following order: Px-control, KME-W, KME-E, and normal-control. Betulin potentiated insulin-stimulated glucose uptake via increased PPAR-γ activity and insulin signaling in 3T3-L1 adipocytes, whereas oleanolic acid enhanced glucose-stimulated insulin secretion and cell proliferation in insulinoma cells. In conclusion, KME-E prevented the deterioration of glucose metabolism in diabetic rats more effectively than KME-W and KME-E can be a better therapeutic agent for type 2 diabetes than KME-W.